De um polo a outro : análise de discursividades sobre transtorno afetivo bipolar em espaços eletrônicos - Fukue, Mário Rafael Yudi (2011)
Inscribed in the French Discourse Analysis, this research studies the process of designation and determination that occurs in discourses of the Internet about the Bipolar Disorder. The discursive process will be analyzed by focusing the articulation between the Medic-Psychiatric Discursive Formation (MPDF) and Religious Discursive Formation (RDR). We choose to analyze the process of designation and determination, since we consider them as the showing place of the fluid language, the imbrication point between language and discourse. For this reason, in Chapter One we navigate on the affluents Language and Historical Materialism . Both of them discharge in the Fluid Language river, as Gadet and Pêcheux conceived in the book La Langue Introuvable . As we were investigating the conditions of discourse production, we formulated a brief thought about cyberculture. The discursive space of this research resides on speeches produced in the Internet. We choose to deal with texts from the Web because we want to contribute with the investigation about the influence of cyberspace in discursive matters. In Chapter Two we navigate on the third affluent, the Theories of Subject river, which also discharges in the Fluid Language river. The Discourse Analysis presumes a subject fragmented by the unconscious (as it was conceived by Lacan). In this chapter we study the philosophical and linguistic discussions about grammatical determination and discursive determination. In Chapter Three we report the methodological procedures of our research and bring the analyses of the corpus. The Discourse Analysis corpus is a temporary instance, which means that it is under constant construction due to the analyst´s action. For this reason, to analyze a discourse is, at some level, to interpret it. From the selected Discursive Formation, we will pay special attention to speeches that contain determinative construction, as substantives, appositions and relative sentence. Our discursive space is limited to speeches taken from medical websites, religious websites, blogs and virtual communities about Bipolar Disorder. We divided the analyses in three discursive sections: the first one deals with the speeches that circulates in the medicpsychiatric discourse formation (MPDF); the second one deals with de speeches that circulates in the religious discourse formation (RDF); and the third section studies the bipolar disorder discourse formation (BDF) and the hiperdiscourse about Bipolar Disorder. In our view, hiperdiscourse is the apparently free discursive side of the hypertext, which reveals the action of the avatar-function (the subject of the hiperdiscourse that uses an avatar in order to write-read in the internet). It is necessary to say that, faithful to the assumptions of the theory that sustain this research, the constitution of the Discursive Formations and their articulations are regulated as gestures of interpretation. In this way, we investigate how the bipolar patient, the Bipolar Disorder, the cure and the treatment are referred to by these several speeches and Discursive Formations. In the same way, we analyze the alliances and antagonism relations in MPDF and RDF that emerges in blogs and virtual communities about Bipolar Disorder in the Web. As an effect of totalization we formulated final considerations in the last section of this research